Gamification: characteristics, trends, risks - A. P. Avdeeva; Yu. A. Safonova (Вестник университета)
Digital technologies development stimulates game elements inclusion into culture and different spheres of society. The identification of regularities and specifics of this process became the purpose of the study. The research methodology was based on the J. Huizing’s “man playing” concept and K. Verbach’s system description of gamification mechanisms. On the basis of these concepts, a grid of typical features of gamification has been compiled and gamification processes in different sociospheres analyzed. The research methods included the emerging gamification practices analysis. Based on the analysis results, trends and risks of implementing the game element into culture have been identified. The complex influence of gamification process on society and culture is manifested by consumers’ demand for interactivity, personal participation, and involvement (immersiveness) in almost all types of activities. These needs are strengthened under the influence of clip culture, making it easier for individuals to assimilate disparate and fragmented pieces of information. The request for immersiveness is closely related to the human need to be the author of the “text”, to control the plot, to create a plurality of readings (hypertext). It has been shown that gamification stimulates innovation in various areas, leads to the emergence of new products, processes, and services. The main risks of gamification development have been highlighted: hyperorientation to entertainment in areas that traditionally involve effort, and manipulation of people’s behavior in areas related to “shoulds”.